REASONS TO DEVELOPMENT OF ASSISTANT PHARMACISTS’ COMPETENCES FOR QUALITY PATIENT CONSULTING IN POLYPHARMACY CASES - Ardava, Elita; Makšāne, Valerija; Šukele, Renāte; Onževs, Oskars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Over fifteen years, polypharmacy has increased by 4.9% across all age groups. Consequently, the responsibility of professionals for advising patients in such cases has increased as well. The research aims at studying patients' habits when purchasing and using medicinal products to enhance the theoretical and practical training of assistant pharmacists at the RSU Red Cross Medical College. The research is based on the patient questionnaires and further analysis of results within a focus group. 404 respondents were interviewed between December 2017 and November 2019. Under the conventions of social studies, this ensured a 3% margin of error at a confidence level of 5%. According to the results of the questionnaire, 44% of the surveyed women and 66% of men were rarely or very rarely interested in the possible side effects of a new medicinal products, food supplement or herbal product. Patients could obtain such information by reading the package leaflet, however, 24% of women and 40% of men read it very rarely or rarely. 30% of respondents used four or more prescription and over-the-counter medical substances on a daily basis. The information-gaining habits of the population regarding side effects and interactions of medicinal products, food supplements and herbal remedies suggest patients must receive oral and more detailed information from a pharmacist. Based on the obtained results, the focus group outlined opportunities for raising pharmacy students' competences.